2020
DOI: 10.1002/open.202000089
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Membrane Types and Catalyst Layers Composition on Performance of Polymer Electrolyte Membrane Fuel Cells

Abstract: Performance of a low temperature polymer electrolyte membrane fuel cell (PEMFC) is highly dependent on the kind of catalysts, catalyst supports, ionomer amount on the catalyst layers (CL), membrane types and operating conditions. In this work, we investigated the influence of membrane types and CL compositions on MEA performance. MEA performance increases under all practically relevant load conditions with reduction of the membrane thickness from 50 to 15 μm, however further decrease in membrane thickness from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…In particular, the molar concentration of H 2 O for Nafion 115 is much smaller than that for the other Nafion membranes. H 2 O flux of PEM as well as the conductivity of the Nafion membrane is promoted when the thickness of the Nafion membrane decreases, particularly below 50 µm [21,47,48], which corresponds to Nafion NRE-212 and Nafion NRE-211 in this study. In addition, the ohmic loss due to proton conductivity of Nafion membrane decreases when the thickness of Nafion membrane [49] decreases.…”
Section: In-plane Distribution Of Mass and Current Density On The Interface Between Nafion Membrane And Anode Catalyst Layer Or The Intermentioning
confidence: 77%
See 1 more Smart Citation
“…In particular, the molar concentration of H 2 O for Nafion 115 is much smaller than that for the other Nafion membranes. H 2 O flux of PEM as well as the conductivity of the Nafion membrane is promoted when the thickness of the Nafion membrane decreases, particularly below 50 µm [21,47,48], which corresponds to Nafion NRE-212 and Nafion NRE-211 in this study. In addition, the ohmic loss due to proton conductivity of Nafion membrane decreases when the thickness of Nafion membrane [49] decreases.…”
Section: In-plane Distribution Of Mass and Current Density On The Interface Between Nafion Membrane And Anode Catalyst Layer Or The Intermentioning
confidence: 77%
“…The thinner Nafion membrane provides lower ohmic losses, indicating that the proton transfers with a shorter distance to reach the cathode and the H 2 O produced in the cathode catalyst layer reaches the anode faster [49]. In addition, H 2 O flux of Nafion membrane as well as the conductivity of the Nafion membrane is promoted when the thickness of the Nafion membrane decreases, especially below 50 µm [21,47,48], which corresponds to Nafion NRE-212 and Nafion NRE-211 in this study. Therefore, it is revealed that the current density increases when the thickness of Nafion membrane decreases, especially for Nafion NRE-212 and Nafion NRE-211.…”
Section: In-plane Distribution Of Mass and Current Density On The Interface Between Nafion Membrane And Anode Catalyst Layer Or The Intermentioning
confidence: 99%
“…Therefore, the ionomer content in the CL plays a crucial role in optimizing MEA performance by simultaneously minimizing losses caused by mass transport as well as electronic and proton conductivity [47][48][49]. In previous work, we found the optimum ionomer to carbon ratio (I/C) is to be dependent on the Pt content of the catalysts and the BET surface areas of the support materials [6,17,50]. Primarily, we found the optimum I/C ratio to be proportional to the BET surface areas of the support materials [6,17].…”
Section: Mea Performance and Diagnosticsmentioning
confidence: 99%
“…Primarily, we found the optimum I/C ratio to be proportional to the BET surface areas of the support materials [6,17]. Yet, when using the same support material, the optimum ionomer amount was inversely proportional to the catalysts' Pt content [50]. Unfortunately, there are no established tools available to define the optimum I/C ratio purely from the material parameters.…”
Section: Mea Performance and Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation